1991
DOI: 10.1002/mcs.1220030505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionic strength of eluent on retention behavior and on the peak broadening process in hollow fiber flow field‐flow fractionation

Abstract: Abstract. The influence of forces on the particles other than the applied cross flow is studied in hollow fiber flow field-flow fractionation (HF'). Such forces can be of either attractive or repelling in nature. It is shown by injecting polystyrene latex beads (0.091 pm in diameter) at different cross flows and by using eluents with different ionic strengths, that there will be disturbances in the concentration profile of the sample irrespective of the type of interacting forces. The retention time and peak b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As FL-70 is a mixture of salt (e.g., sodium carbonate) and surfactant ( e.g ., oleic acid, polyoxyethylene alcohols and poly­(ethylene glycol) (Technical Note, Chemistry Division, Fisher Scientific Co.), the change in separation resolution might be attributed to the variation of ionic strength and surfactant. To some extent, the ionic strength in the media dominates the electrical double layer of both nanoparticles and channel wall, which controls the particle–particle and particle–wall interactions . To verify the effect of ionic strength, NaClO 4 solutions with various concentrations (0–1%, w/v) were introduced into the system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As FL-70 is a mixture of salt (e.g., sodium carbonate) and surfactant ( e.g ., oleic acid, polyoxyethylene alcohols and poly­(ethylene glycol) (Technical Note, Chemistry Division, Fisher Scientific Co.), the change in separation resolution might be attributed to the variation of ionic strength and surfactant. To some extent, the ionic strength in the media dominates the electrical double layer of both nanoparticles and channel wall, which controls the particle–particle and particle–wall interactions . To verify the effect of ionic strength, NaClO 4 solutions with various concentrations (0–1%, w/v) were introduced into the system.…”
Section: Resultsmentioning
confidence: 99%
“…To some extent, the ionic strength in the media dominates the electrical double layer of both nanoparticles and channel wall, which controls the particle−particle and particle−wall interactions. 44 To verify the effect of ionic strength, NaClO 4 solutions with various concentrations (0−1%, w/v) were introduced into the system. Results showed that addition of NaClO 4 had little impact on both separation resolution and peak widths, except for the slight decrease in t R .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Besides these rectangular channel systems, the first experimental work on using a hollow fiber membrane as a cylindrical channel was reported by Lee et al, and this idea was suggested to be a good alternative to the conventional flow FFF channel by Doshi and Gill . A series of works reported on the feasibility of using hollow fiber for the separation of polystyrene latex standards, , with the investigation of ionic strength effect of carrier solution, properties of fiber membrane, and the overloading effect in hollow fiber flow FFF (HF-FlFFF) runs . Recent attempts have been made at the separation of proteins and water-soluble polymers .…”
mentioning
confidence: 99%
“…8 Jönsson and Carlshaf applied the system to separation of polystyrene latex beads studying sample overloading, the influence of ionic strength of the solvent and the properties of various fiber types. [9][10][11] In 1995 Wijnhoven et al applied the same HF 5 system to separate polystyrene sulfonate and to investigate watersoluble polymers. 12,13 Recently, it has been reported that particle separation by HF-FlFFF can be greatly improved to the resolution level normally achieved by a rectangular system by optimization.…”
Section: Introductionmentioning
confidence: 99%